Drug-excipient and drug-drug mixtures : a pathway for the production of co-amorphous entities - Costa, Nuno F. da (2019)
Abstract of the communication presented at the 3rd International Congress of CiiEM ‘Research and Innovation in Human and Health Sciences’. Campus Egas Moniz, Caparica, Portugal, June 20-22, 2018